Ileus Ascariasis: Perspektif Integratif antara Aspek Klinis, Diagnostik, dan Strategi Tatalaksana - I Nyoman Dwi Suputra Diarsa (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2026)
Background: Ileus ascariasis is a severe complication of Ascaris lumbricoides infection, predominantly affecting children in endemic regions with poor sanitation. Despite global control programs, it continues to cause significant morbidity and mortality, yet fragmented evidence limits comprehensive understanding. This review was conducted to integrate clinical, diagnostic, management, and preventive perspectives. Methods: A structured literature search was performed across PubMed, Scopus, ScienceDirect, Google Scholar, and additional sources using boolean operators. Eligible publications included case reports, original studies, reviews, clinical guidelines, and public health reports in English and Indonesian. Evidence was synthesized narratively and thematically by an academic team under faculty supervision. Discussion: The review highlights that ileus ascariasis typically manifests as small bowel obstruction caused by worm boluses, sometimes complicated by volvulus, intussusception, or perforation. Diagnostic modalities such as ultrasonography and CT scans are useful but limited in accessibility within resource-constrained settings. Management ranges from conservative approaches, including decompression, and antibiotics, to surgical intervention when obstruction persists or complications occur. Preventive strategies such as mass drug administration, sanitation improvement, and health education show potential but are challenged by reinfection, low awareness, and uneven implementation. Knowledge gaps remain regarding optimal diagnostic pathways, comparative effectiveness of conservative and operative strategies, also integration of prevention with community-based programs. Conclusion: Ileus ascariasis is both a clinical emergency and a persistent public health concern. Strengthening early detection, optimizing treatment protocols, and linking preventive measures with sustainable community interventions are crucial to reducing its impact on vulnerable populations.